More Dubious Dead Sea Scrolls: Four Pre-2002 Fragments in the Schøyen Collection - Justnes, Årstein (Dead Sea discoveries, 2021)
Abstract In the course of the last eighteen years more than 75 new “Dead Sea Scrolls” fragments have surfaced on the antiquities market. These are commonly referred to as post-2002 Dead Sea Scrolls-like fragments. A growing number of scholars regard a substantial part of them as forgeries. In this article, we will discuss four more dubious fragments, but this time from the 20th Century—or at least from pre-2002 . Two of the fragments have been known since the late nineties and are published in the DJD series. One was published in Revue de Qumran (2003), and one in Gleanings from the Caves (2016). All four are today accepted as part of the Dead Sea Scrolls dataset even though they are unprovenanced and have made-up—or at least very adaptable—lists of previous owners. In this article, we will critically review their provenance and discuss the lack of proper interest in provenance on the part of the collector who owns them and the scholars who published them.